High- and Low-Contrast Letter Acuity Perception Matures With Age in Normally Sighted Children. Issue 2 (June 2020) - Waldman, Amy T.; Lavery, Amy M.; Liu, Geraldine W.; Avery, Robert A.; Liu, Grant T.; Maguire, Maureen G.; Ying, Gui-shuang; Banwell, Brenda L.
Abstract : Background: High-contrast visual acuity (HCVA) changes with age, yet little is known about pediatric-specific age- and sex-normative values for low-contrast letter acuity (LCLA). We define maturational changes in monocular and binocular HCVA and LCLA in childhood and adolescence. Methods: Normally sighted youth (ages 5–20 years, without neurologic or ophthalmologic disease and best-corrected HCVA of 20/25 or better in each eye) were recruited. Mean monocular and binocular scores using Early Treatment Diabetic Retinopathy Study (for HCVA) and 2.5% and 1.25% Sloan (for LCLA) charts and the magnitude of binocular summation were calculated using 2-year bins. Relationships between scores and age were explored using scatterplots with Locally Weighted Scatterplot Smoothing (LOWESS) and analysis of variance that accounts for intereye correlation, followed by test of linear trend for age effect. Results: Among 101 (202 eyes) healthy participants (mean age 13 years, 42% males), monocular and binocular scores varied by age, with highest mean scores achieved in the 13 to 14–year age group for both HCVA and LCLA. Between the ages of 5 and 14.9 years, monocular scores increased linearly with age (0.76 letter/year for HCVA, 1.11 letters/year for 2.5% LCLA, and 0.97 letter/year for 1.25% LCLA; all P < 0.0001). Binocular HCVA scores also increased with age between 5 and 14.9 years (0.71 letters/year, P < 0.0001). The magnitude of binocular summation for HCVA or LCLA did not change with age. Conclusions: HCVA and LCLA abilities mature into adolescence, peak between 13 and 14.9 years of age, and then plateau into adulthood. Evaluation of patients with visual deficits should consider age-expected normal visual acuity.